Study on the effect of family multi-modal rehabilitation exercise on non-motor symptoms of patients with Parkinson's disease (家庭多模式康复运动对帕金森病患者非运动症状的影响研究) - HE Xingping (何兴萍); GUO Wei (郭伟); HUANG Ling (黄凌); YANG Jiajia (杨佳佳); LIU Jiangbing (刘姜冰) (中西医结合护理)
Objective To exploring the effect of family multi-mode rehabilitation exercise on non-motor symptoms of Parkinson's disease patients. Methods Totally 80 Parkinson's disease patients were recruited as the research objects. According to whether to conduct family multi-mode rehabilitation exercise guidance, the patients were divided into control group (n=32) and study group(n=48). All patients were given conventional intervention treatment, and those in the study group were given family multi-modal rehabilitation exercise guidance. The non-motor symptoms, cognitive ability and ability of daily living of the two groups were evaluated. Results The score of non-motor symptoms questionnaire (NMS-Quest) was decreased in both two groups after intervention, and was lower in the study group than that in the control group (P＜0. 05). The score of mini-mental state examination(MMSE) was increased in both two groups after intervention, and was higher in the study group than that in the control group (P＜0. 05). The score of Activity of Daily Living (ADL) was decreased in both two groups after intervention, and was lower in the study group than that in the control group (P＜0. 05). Conclusion Family multi-mode rehabilitation exercise can significantly improve patients' non-motor symptoms and mental state, and improve patients' ability of daily living, which is worthy of being widely used in clinical practice. (目的 探讨家庭多模式康复运动对帕金森病患者非运动症状的影响效果。方法 选取2018年1月—2019年8月扬州大学附属医院接收治疗的80例帕金森病患者作为研究对象, 按是否进行家庭多模式康复运动指导将患者分为对照组32例和研究组48例。对照组予以常规干预治疗, 研究组在对照组基础上予以家庭多模式康复运动指导。观察2组患者干预前后非运动症状情况、认知能力及日常生活能力。结果 干预后, 2组患者非运动症状问卷量表(NMSQuest)评分均降低, 且研究组评分低于对照组, 差异具有统计学意义(P＜0. 05)。干预后, 2组患者精神状态检查量表(MMSE)评分均升高, 且研究组评分高于对照组, 差异有统计学意义(P＜0. 05)。干预后, 2组患者日常生活能力量表(ADL)评分均降低, 且研究组评分低于对照组, 差异有统计学意义(P＜0. 05)。结论 家庭多模式康复运动可明显改善患者非运动症状及精神状态, 提高患者日常生活能力, 值得在临床上广泛应用。)